Measuring the impact of burn scarring on health-related quality of life: Development and preliminary content validation of the Brisbane Burn Scar Impact Profile (BBSIP) for children and adults. Issue 7 (November 2015) - Tyack, Zephanie; Ziviani, Jenny; Kimble, Roy; Plaza, Anita; Jones, Amber; Cuttle, Leila; Simons, Megan
Highlights The Brisbane Burn Scar Impact Profile (BBSIP) was developed. The BBSIP is a measure of burn-scar specific health-related quality of life. Unique items of the impact of burn scars were developed from patient-report. The measure was designed to be suitable for use in clinical trials. Preliminary content validation of the profile was supported.